Achieving high energy transfer efficiency in Sr6Ca4(PO4)6F2:Ce3+, Mn2+ by regulating the occupation of activator. (July 2019) - Li, Yuebin; Wang, Zhijun; Guan, Mengyuan; Liu, Jinjin; Meng, Xiangyu; Wang, Zhipeng; Qiu, Keliang; Li, Xue; Yang, Zhiping; Li, Panlai
Graphical abstract: Highlights: Discussing the reasons for the red-shift of Ce 3+ emission: reabsorption and non-radiative relax of Ce 3+ ions, crystal field splitting and nephalauxetic effect. The priority occupation of Mn 2+ is analyzed and the concentration quenching effect between activator ions was reduced by introducing Mg 2+ . A high energy transfer efficiency from Ce 3+ to Mn 2+ is achieved by reducing the energy loss. Abstract: Series of color tunable Sr6 Ca4 (PO4 )6 F2 :Ce 3+, Mn 2+ were achieved. In the way of energy transfer, the activator Mn 2+ should get large energy from sensitizer Ce 3+ and show high efficiency. However, with increasing Mn 2+ concentration the emission intensity of Ce 3+ decreases rapidly, the emission intensity of Mn 2+ shows unapparent increase. It indicates that there are lots of energy losses in the process of energy transfer from Ce 3+ to Mn 2+ . With the high concentration of Mn 2+, the severe concentration quenching effect of Mn 2+ occurs in Sr6 Ca4 (PO4 )6 F2 :Ce 3+, Mn 2+ . In order to reduce the energy loss owing to the concentration quenching effect, Mg 2+ ions are introduced into Sr6 Ca4 (PO4 )6 F2 :Ce 3+, Mn 2 to regulate the occupation of Mn 2+ . Consequently, the distance between Mn 2+ increases and the energy loss between Mn 2+ is effectively reduced. Therefore the emission intensity of Mn 2+ increases greatly, and high energy transfer efficiency of Ce 3+ →Mn 2+ is achieved.